Transformasi Bimbingan Dan Konseling Era Pandemi - Alam, Fiptar Abdi; Akhmadi, Agus (Balai Diklat Keagamaan Surabaya, 2021)
Guidance and counseling service innovation in the pandemic era is a necessity. Guidance and counseling services are carried out online, becoming a service model that is widely applied in madrasas. This study aims to describe the innovation of guidance and counseling services in madrasas. This study uses a survey approach and literature review. A literature review was carried out to examine various innovations in counseling services during the pandemic, while the difficulties of students in online-based counseling services were carried out in a survey. Research respondents are 383 students who receive online guidance and counseling services at Madrasah Tsanawiyah. Data collection was carried out by means of questionnaires and interviews with 30 Guidance and counseling teachers. The research instrument was sent by uploading a google form to the respondent. Data processing was carried out by descriptive statistics, while the data from interviews were analyzed deductively and qualitatively. The results showed that the innovation of guidance and counseling services was carried out on student needs assessment activities, counseling services, group guidance and classical services. The online service media used are Telephone, Video Call, WA, Facebook Messenger, e-learning, Google class, Youtube live streaming, Zoom, Google Meet which connects Guidance and counseling teachers with students. The process of online guidance and counseling services at madrasas is fun and easy and effective for students. In the implementation of online services, there are still obstacles in the guidance and counseling service infrastructure.